Incidental Detection and Surgical Management of Unilateral Synovial Lipomatosis in a Total Knee Replacement Case: A Case Report - Vidhyadhar Wadkar; PN Kulkarni (Journal of Neonatal Surgery, 2024)
Background: Synovial lipomatosis is a rare, benign condition characterized by adipose tissue proliferation within the synovial membrane, most commonly affecting the knee joint. It can lead to symptoms such as joint pain, swelling, and restricted mobility, often mimicking other joint pathologies. This study reports an incidental intraoperative finding of unilateral synovial lipomatosis during a total knee replacement (TKR) procedure in a patient with advanced osteoarthritis. Objective: To describe the clinical presentation, diagnostic process, surgical management, and post-operative outcomes of synovial lipomatosis discovered during TKR. Methods: A 43-year-old male presented with bilateral knee pain, swelling, and limited movement due to tri-compartmental osteoarthritis. Pre-operative imaging included X-rays and MRI, which showed significant osteoarthritic changes along with abnormal fatty projections in the synovium. During TKR, lipomatous masses were observed intraoperatively, leading to excision of the affected tissue. Histopathological examination confirmed the diagnosis of synovial lipomatosis. Post-operative assessment included imaging and clinical follow-up. Results: MRI confirmed villous projections with fat signal intensity, characteristic of synovial lipomatosis. Histology revealed mature adipocytes without atypia, supporting the diagnosis. Post-operatively, the patient showed marked pain reduction, improved range of motion, and no recurrence of swelling or effusion. Conclusion: This case underscores the importance of thorough pre-operative imaging and careful intraoperative assessment in patients with atypical joint symptoms. TKR combined with resection of synovial lipomatous tissue effectively relieved symptoms and improved knee function. Awareness of synovial lipomatosis as a possible differential in knee pathologies can improve diagnosis and management outcomes. Future studies are needed to further understand the etiology and recurrence rates of this condition.